Accumulation and exportation of macronutrients in beet under different managements of fertigation and salinity - Silva, Alexsandro Oliveira da; Franca e Silva, Enio Farias de; Klar, Antonio Evaldo [UNESP] (Inst Agronomico, 2017)
Fertigation is a major form of fertilizer installments; however, if applied in excess, the fertilizers can damage the crop development. The objective of this study was to evaluate the accumulation and exportation of macronutrients in a beet cultivation under 2 fertigation managements at different levels of soil salinity. The experiment was conducted in a greenhouse in the city of Botucatu, Brazil. The treatments consisted of the combination of soil salinity ( 1.0, 3.0, 6.0, 9.0 and 12.0 dSu m(-1)), fertigation management ( M-1 = traditional and M-2 = control of the ionic concentration), and varieties of beets ( C-1 = Early Wonder and C-2 = Itapua) in a 5 x 2 x 2 factorial design with 4 replications in randomized blocks. After harvest, it was determined the accumulation of macronutrients ( N, P, K, Ca, Mg, P, and S mgu plant(-1)). There was an increased accumulation of nutrients studied for both cultivars and fertigation managements until electrical conductivity levels between 3 ( M-1) and 6 ( M-2) dS.m(-1). The order of macronutrients exportation was different for the studied cultivars. The cultivar Early Wonder followed the following order: K > N > Ca > Mg > P > S, while, for the Itapua cultivar, the order was K > N > Mg > Ca > S > P.
Keywords: Beta vulgaris L.; electrical conductivity; fertilizers